A Graphical Pressure Sensor Array with Multilayered Structure Based on Graphene and Paper Substrate. Issue 2 (9th November 2021) - Ji, Chao; Zhang, Qiang; Li, Qiang; Pei, Zhen; Zhao, Dong; Yuan, Zhongyun; Wang, Jie; Cheng, Yongqiang; Zhang, Wendong; Sang, Shengbo
Abstract: Paper‐based flexible pressure sensors have received extensive attention owing to their recoverability and accessibility. This study, proposes a graphical pressure sensor array with a multilayered structure. A simple writing method is adopted to realize the adsorption of sensitive materials on the fiber structure of cellulose paper. Pressure sensors with 1, 3, 5, and 7 stacked layers are fabricated and compared. The results show that the seven‐layer sensor achieves a high sensitivity (44 kPa –1 ) and fast time response (less than 150 ms). The highly sensitive stacked paper‐based sensor array realizes the pressure detection in objects and special‐shaped surfaces. A pressure sensor based on a commercial corrugated box is also fabricated for comparison. The corrugated carton array is used to switch the reminder devices for convenience and accessibility. Because many scenarios require a safe distance to be maintained, particularly under the influence of COVID‐19, the writable paper‐based sensor array is used to realize graphical distance perception and provide warnings. Abstract : A graphical pressure sensor can be fabricated by attaching graphene to a cellulose substrate through a writing method. Based on the piezoresistive property of this sensor, it can be made as a safety warning device in life, especially under the influence of the COVID‐19, to remind people to keep distance.